High performance 4.7 THz GaAs quantum cascade lasers based on four quantum wells. (2nd December 2016) - Ohtani, Keita; Turčinková, Dana; Bonzon, Christopher; Benea-Chelmus, Ileana-Cristina; Beck, Mattias; Faist, Jérôme; Justen, Matthias; Graf, Urs U; Mertens, Marc; Stutzki, Jürgen
Abstract: GaAs/AlGaAs quantum cascade lasers based on four quantum well structures operating at 4.7 THz are reported. A large current density dynamic range is observed, leading to a maximum operation temperature of 150 K for the double metal waveguide device and a high peak output power more than 200 mW for the single surface plasmon waveguide device. A continuous wave, single mode, third order distributed feedback laser with a low electrical power dissipation and a narrow far-field beam pattern, which is required for a local oscillator in astronomy heterodyne spectrometers, is also demonstrated.